2018
DOI: 10.1080/10245332.2018.1461292
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of liver and cardiac iron overload using MRI in patients with chronic anemias in Latin American countries: results from ASIMILA study

Abstract: A high prevalence of iron overload in this patient population in Latin American countries indicates that a better diagnosis and management of iron overload is required in these countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Previous literature shows a moderate correlation between liver iron concentration and SF in MDS patients [15]. Our study confirms that ASF correlates with liver T2*and cardiac T2*, but there is no significant correlation between cardiac T2* and liver T2*, and the correlation coefficients between ASF and cardiac are significantly higher than those in the liver.…”
Section: Discussionsupporting
confidence: 83%
“…Previous literature shows a moderate correlation between liver iron concentration and SF in MDS patients [15]. Our study confirms that ASF correlates with liver T2*and cardiac T2*, but there is no significant correlation between cardiac T2* and liver T2*, and the correlation coefficients between ASF and cardiac are significantly higher than those in the liver.…”
Section: Discussionsupporting
confidence: 83%
“…In a post-hoc analysis of the EPIC study, patients with AA were seen to have had an average of between 8 and 15 transfusion sessions in the previous year, and their median ferritin levels were 3,600-3,700 ng/ml (73). Using imaging techniques (MRI), IOL was observed in the liver in 76.4% of patients (including AA) and in the heart in 19.2% (74). The presence of an IOL in patients with severe AA reduces the efficacy of the immunosuppressive therapy and increases the risk of a relapse, confirming that it is a negative prognostic factor for the outcome of these patients (75).…”
Section: Utility Of Iron Chelation In Aplastic Anemiamentioning
confidence: 99%
“…The EPIC prospective study evaluated the efficacy and safety of ICT with deferasirox in 116 patients with AA (74). The analysis showed that therapy with deferasirox efficaciously reduced median serum ferritin levels: this efficacy was associated with the transfusional iron load and the dose of deferasirox, with higher doses of medicinal product needed to reduce the iron load in subjects with a high intake (79).…”
Section: Utility Of Iron Chelation In Aplastic Anemiamentioning
confidence: 99%
“…The liver is the main location for iron storage and is the earliest and most critical organ for iron deposition. 5 Excess accumulation of iron may lead to life-threatening complications, including liver fibrosis, cirrhosis, liver failure, and hepatocellular carcinoma. 6…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the main location for iron storage and is the earliest and most critical organ for iron deposition. 5 Excess accumulation of iron may lead to lifethreatening complications, including liver fibrosis, cirrhosis, liver failure, and hepatocellular carcinoma. 6 The gold standard method to measure liver iron concentration is a biopsy; however, a liver biopsy is invasive and susceptible to sample variability from uneven hepatic iron concentration.…”
Section: Introductionmentioning
confidence: 99%